Sistem Perhitungan Pembiayaan MurᾹbahah Dalam Pandangan Hukum Ekonomi Syariah (Studi Kasus Bmt Sakinah Bekonang) - sari, anisa nurina; , Dr. Supawi Pawenang SE.MM (2016)
Murābaḥa in the concept of fiqh is buying and selling at the initial price (principal) with an additional advantage. This concept has been widely used by banks and Islamic financial institutions to finance working capital and financing members (customers) trade. This study has aimed to find out how the calculation system of murābaḥa financing at BMT Sakinah Bekonang. As Discussed in this thesis is the calculation procedures and systems of murābaḥa financing itself in BMT Sakinah Bekonang. This research is descriptive qualitative, some methods of collecting data have been used they are interview, observation, and literature. The Interview has been applied to the staff of financing of the BMT Sakinah, while the observation has been used for observing the performance of BMT. In addition to using the both methods the researchers has used the scientific literature by reading books concerned with the title. For analyzing data, has been used a descriptive method, either inductive or deductive. From data analyzing, it is known that the murābaḥa financing calculation system in BMT Sakinah is in conformity with the existing principles. It proved there is no element of riba and hide advantage of member (customer), and in accordance with the DSN MUI fatwa. Keywords: Murābaḥa Financing Calculation, Riba, shari'ah Economic law.